Kinematic and neuromuscular measures of intensity during drop jumps in female volleyball players - Torres-Banduc, M.; Ramirez-Campillo, R.; Andrade, D. C.; Calleja-González, J.; Nikolaidis, P. T.; McMahon, J. J.; Comfort, P. (Frontiers in Psychology, 2021)
The aim of this study was to assess drop jump (DJ) performance variables (jump height, contact time, and reactive strength index) concomitant to surface electromyography (sEMG) of lower limb muscles during DJs from different drop heights (intensities). The eccentric and concentric phase sEMG from the gastrocnemius medialis, biceps femoris, and vastus medialis muscles were assessed during all tests, with sEMG activity normalized to maximal voluntary isometric contraction (MVIC). In a cross-sectional, study, 10 amateur female volleyball players (age 22.1 ± 1.8 years; body mass 72.9 ± 15.2 kg; height 1.70 ± 0.08 m) completed DJs from six heights [15-90 cm (DJ15 to DJ90)]. During DJs there was no jump-target box to rebound on to. Results of one-way analysis of variance (ANOVA) showed that the jump height, contact time, and reactive strength index were not significantly (p > 0.05) different between drop heights. Mean biceps femoris eccentric and concentric sEMG ranged from 27 to 50%, although without significant differences between drop heights. Mean gastrocnemius medialis eccentric and concentric sEMG remained relatively constant (~60-80% MVIC) across DJs heights, although eccentric values reached 90-120% MVIC from DJ75 to DJ90. Mean variations of ~50-100% MVIC for eccentric and ~50-70% MVIC for concentric sEMG activations were observed in the vastus medialis across DJs heights. The biceps femoris eccentric/concentric sEMG ratio during DJ45 (i.e., 1.0) was lower (p = 0.03) compared to the ratio observed after DJ90 (i.e., 3.2). The gastrocnemius medialis and vastus medialis eccentric/concentric sEMG ratio were not significantly different between drop heights. In conclusion, jumping performance and most neuromuscular markers were not sensitive to DJ height (intensity) in amateur female volleyball athletes.